Impact of pay revision on state government's finances - Bajaj, J.L. (1999)
The gross fiscal deficit of state governments has been about 3 per cent of GDP in the 1990s. But this is likely to increase substantially as a result of the implementation of the recommendations of the Pay Commission for central government employees. According to one estimate,if the salaries of the employees of state governments, state financial and aided educational institutions, local bodies and state-owned enterprises are revised to the level of central government employees, the revenue expenditure of the state governments will increase by Rs.20,000-30,000 crore a year. This would create a major imbalance in their resources. How the state governments plan to finance this expenditure is an important question. This paper studies the impact of pay revision on the finances of the governments of Uttar Pradesh, Madhya Pradesh and Maharashtra. - Reproduced
Keywords: Civil service - Salaries, etc; Public finance; Civil service